Clinical outcome comparison between LaPrade and Larson’s technique for posterolateral corner injury of knee - Kolusu, Natesh; Aravind, G.; Brungi, Venkatesh (International Journal of Research in Orthopaedics, 2021)
Background: The knee joint is the largest synovial joint in the body. It is a modified hinge joint. It is a tri axial joint consisting of three articulations, patella-femoral, medial tibio-femoral and lateral tibio-femoral joint. The posterolateral corner (PLC) is often called the “dark side” of the knee due to its complexity and the minimal amount of research performed to better understand its anatomy and biomechanics. The present study was conducted to analyse the postoperative clinical outcome of Larson’s technique in one group and LaPrade technique in another group and elucidating which technique best restores stability and function to an isolated PLC injury. Methods: This was a prospective study involving 40 patients with postero-lateral corner injuries (PCL) divided into two groups of 20 patients each. Larson’s reconstruction and LaPrade’s reconstruction techniques were done and the clinical outcomes were analyzed. Results: Mean postoperative Lysholm score for Larson group was 78.10±10.26 with scores ranging from 58-92 with median value of 80.0. Mean postoperative Lysholm score for LaPrade group was 85.7±8.802 with scores ranging from 60-96 with median value of 87.0. Mean postoperative IKDC score for Larson group was 74.0±8.93 with scores ranging from 60-90 with median value of 75.0. Mean postoperative IKDC score for LaPrade group was 84.9±5.67 with scores ranging from 73-92 with median value of 85.5. This study recorded similar outcomes in both the groups. Conclusions: The posterolateral knee reconstruction techniques presented here significantly improved objective stability in patients with a chronic posterolateral knee injury.